Produção e utilização de anticorpos IgY para diagnóstico de brucelose - Soares, Pollyanna Mafra (2013)
The dissertation was divided into five chapters. The first was called \"General Consideration,\" which was performed a brief literature review about what was proposed in the work. In the second chapter aimed to check whether chickens immunized with Brucella abortus B19 vaccine and soluble protein extract solution, extracted from this vaccine, could produce specific polyclonal antibodies, detectable in indirect ELISA tests. Six hens with 25 week-old, White Leghorn breed, were immunized, two immunized with B19, two with a soluble protein extract solution extracted from the B19 vaccine and two were used as controls, being immunized with PBS. Blood samples were taken fortnightly and eggs daily for 13 weeks. Polyclonal antibodies IgY were purified from egg yolk using for delipidation the dilution method in acidified water (pH 5,0-5,2) and precipitation with ammonium sulfate. Was performed ELISA test to verify the specificity of IgY. Was possible to observe the production of specific polyclonal antibodies against the antigens used in the immunizations, both in serum and in egg yolks. In the third chapter aimed to check the response of IgY extracted from egg yolk of immunized chickens with B19 vaccine (IgY anti- B19) against the antigen EPS and the response of IgY extracted from egg yolk of immunized chickens with EPS (IgY anti-EPS) against the vaccine antigen B19, using the ELISA in order to verify possible antigen-antibody interactions. For this, two microtiter plates were sensitized, in one of them using B19 vaccine as antigen and another EPS antigen, were placed on each plate as primary antibodies IgY extracted from the egg yolk, for each group of immunized hens, a group immunized chickens with vaccine B19, one with EPS and one control. Both IgY anti-B19, as IgY anti-EPS were reactive to the antigens tested, so it is believed that these antibodies may serve as a tool for the identification of antigens in diagnostic tests aimed at this purpose. The objective of fourth chapter was to evaluate the humoral immune response of cattle naturally infected and newly vaccinated with B19 vaccine against EPS and B19 vaccine antigens in indirect ELISA. Was used in this study 96 samples of blood serum of cattle, 32 heifers recently vaccinated with B19 vaccine, 32 naturally infected cattle and 32 negative cattle for brucellosis. Was verified that in the indirect ELISA with antigen EPS when compared with indirect ELISA with antigen vaccine B19 and 2-ME, this test was able to distinguish newly vaccinated animals of naturally infected animals. The fifth chapter are the \"final thoughts\" on the entire dissertation, including findings of all the chapters.